A Theoretical and Experimental Study to Optimize Cell Differentiation in a Novel Intestinal Chip - Langerak, Nicky; Ahmed, Haysam M. M.; Li, Yang; Middel, Igor R.; Eslami Amirabadi, Hossein; Malda, Jos; Masereeuw, Rosalinde; van Roij, René (Frontiers in Bioengineering and Biotechnology, 2020)
Microphysiological systems have potential as test systems in studying the intestinal barrier, in which shear stress is critical for the differentiation of Caco-2 cells into enterocytes. The most commonly used in vitro gut model for intestinal barrier studies is based on trans-well cultures. Albeit useful, these culture systems lack physiological shear stress which is believed to be critical for the differentiation of Caco-2 cells into enterocytes and to form tight monolayers. Conversely, organ-on-chip models have presented themselves as a promising alternative since they provide cells with the required shear stress. To this end, a novel biocompatible 3D-printed microfluidic device was developed. In this device, Caco-2 cells were seeded under physiologically-relevant unidirectional shear stress and compared to cells cultured under gravity-driven flow. Using numerical studies, the flow rate that corresponds to the required shear stress was calculated. Experimental tests were conducted to verify the effect of this on cell differentiation. The experiments clearly showed an enhancement of cell differentiation potential in a unidirectional physiologically relevant pump-driven flow system (PDFS) as opposed to the simpler bidirectional gravity-driven flow system (GDFS). Additionally, computational modeling of an adapted design confirmed its ability to supply all cells with a more homogeneous shear stress, potentially further enhancing their differentiation. The shear stress in the adapted design can be well approximated with analytic methods, thus allowing for efficient predictions for all parameter values in the system. The developed novel microfluidic device led to the formation of a tighter monolayer and enhanced functional properties of the differentiated Caco-2 cells, which presents a promising tool for preclinical in vitro testing of drugs in an animal-free platform.